Toxicity And Sublethal Effects Of Artemisia annua Linnaeus On Aedes aegypti (Linnaeus), Aedes albopictus (Skuse), Anopheles sinensis Wiedemann And Culex quinquefasciatus Say - Cheah, Shao Xiong (2014)
Artemisia annua is well known for its strong antimalarial properties; however, limited studies were conducted on the effects of the plant against mosquitoes. This study focuses on the larvicidal activity and sublethal effect of a crude extract of A. annua against Aedes aegypti, Aedes albopictus, Anopheles sinensis and Culex quinquefasciatus, and its effect on the oviposition and the ovicidal activities of the mosquitoes. Artemisia annua adalah terkenal dengan ciri-ciri anti-malarianya tetapi kurang kajian dijalankan mengenai kesan tumbuhan ini terhadap nyamuk. Kajian ini bertumpu ke atas aktiviti larvisid dan kesan submaut ekstrak mentah A. annua terhadap Aedes aegypti, Aedes albopictus, Anopheles sinensis dan Culex quinquefasciatus, dan kesan ke atas aktiviti bertelur dan ovisid pada nyamuk tersebut.